Your Name Is Your Blessing: Hebrew Names and Their Mystical Meanings - Blech, Benjamin; Blech, Elaine (Jason Aronson, 2012)
Your Name Is Your Blessing: Hebrew Names and Their Mystical Meanings represents the first time that the secrets of the Kabbalah, the mystical teachings of Jewish spiritual leaders, were introduced to the general public for the purpose of explaining the profound meanings hidden in every person’s name. Even now, Your Name is Your Blessing remains alone in its application of Kabbalistic teachings to the choice and understanding of one’s name. A name tells a story that captures a person’s character and personality, and Your Name Is Your Blessing, Benjamin and Elaine Blech provide a guide to understanding what your name says about you and your life. The Blechs give the gematria—the total numerical value of a word, which is the starting point for kabbalistic analysis—for hundreds of names, as well as Biblical words, phrases, and blessings associated with this numerical value.